2016
DOI: 10.1007/s40069-016-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Ratio of Concrete Beams Internally Prestressed with Unbonded CFRP Tendons

Abstract: The compression or tension-controlled failure mode of concrete beams prestressed with unbonded FRP tendons is governed by the relative amount of prestressing tendon to the balanced one. Explicit assessment to determine the balanced reinforcement ratio of a beam with unbonded tendons (q U pfb) is difficult because it requires a priori knowledge of the deformed beam geometry in order to evaluate the unbonded tendon strain. In this study, a theoretical evaluation of q U pfb is presented based on a concept of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…As a result, the calculation of the balanced reinforcement ratio for beams with unbonded tendons requires further consideration. Lee et al [28] found that the balanced reinforcement ratio of a beam with unbonded tendons ( ) was always smaller than that of a beam with ρ specimens considered in their study.…”
Section: Experimental Results 31 Failure Modesmentioning
confidence: 69%
“…As a result, the calculation of the balanced reinforcement ratio for beams with unbonded tendons requires further consideration. Lee et al [28] found that the balanced reinforcement ratio of a beam with unbonded tendons ( ) was always smaller than that of a beam with ρ specimens considered in their study.…”
Section: Experimental Results 31 Failure Modesmentioning
confidence: 69%
“…Heo et al tested the flexural behaviors of the monolithic beam prestressed with the internal unbonded CFRP tendon [24,40], in which the specimens RU50 and RO50 were designed with the same dimensions but different prestressing reinforcement ratios. These two specimens are employed here to verify the effectiveness of the proposed model for the simulation of internal unbonded tendons.…”
Section: Verification For Tests Of Monolithic Beam Prestressed With I...mentioning
confidence: 99%
“…The application of prestressed CFRP tendons to SRC structures could greatly improve their crack resistance and minimize their deflection under service loads while providing additional rigidity. Extensive works have been carried out on the bending behaviour of prestressed CFRP tendon steel reinforced concrete (PSRC) members [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%